Health benefits of fish and fish by-products—a nutritional and functional perspective - Noreen, Sana; Hashmi, Bushra; Aja, Patrick Maduabuchi; Atoki, Ayomide Victor (Frontiers in Nutrition, 2025)
Fish is the primary marine source that provides adequate nutrition to the human body. Fish production is increasing every year, contributing to a sustainable economy, as they provide a significant source of income and food: This review highlights the potential health benefits, industrial applications, and toxicity of various fish species Globally, fish possess various bioactive compounds; this efficacy makes them a more edible source to consume worldwide. A wide range of bioactive compounds, primary macronutrients, micronutrients, vitamins, and minerals are present in various fish types that are essential in preventing different human disorders. The nutritional value of fish helps to provide exceptional health benefits against different human ailments. Fish are excellent sources of protein, peptides, and polyunsaturated fatty acids, particularly eicosapentaenoic acid (EPA), Alpha-linolenic acid (ALA), omega-6 fatty acids, and docosahexaenoic acid (DHA), omega-3 fatty acids that influence human health positively. Fish and their by-products are also excellent sources for developing various nutraceutical and functional foods to fight against multiple human disorders. The by-products of fish exert significant effects against infection, viral attack, cardiovascular diseases, immune disorders, oxidative stress, inflammation, neurological diseases, and other physiological complications. Few fish species are contaminated with harmful substances that cause potential risks to children's and adults' bodies. Additionally, the therapeutic use of fish and their by-products unveils the potential nutritional benefits to reduce the burden on public health by managing dietary issues such as food security, protein deficiency, and other nutritional-related problems.